Tuning microstructure and mechanical properties of open porous TiNb and TiFe alloys by optimization of dealloying parameters. (September 2018) - Okulov, I.V.; Okulov, A.V.; Volegov, A.S.; Markmann, J.
Abstract: Here, we developed open porous TiFe and TiNb alloys by liquid metal dealloying. Tuning dealloying parameters allows controlling phase formation and microstructure of the resulting structures. Particularly, α ″ martensite together with β -Ti and single phase β -Ti form in TiNb obtained by dealloying of its precursor at 1073 K and 1173 K, respectively. The yield strength of porous TiFe reaches up to 150 MPa. Impregnation by polymers of porous alloys leads to further increasing of their yield strength up to 260 MPa. Remarkably, the Young's modulus of the materials studied remains below 5.2 GPa irrespective of the achieved strength. Graphical abstract: Unlabelled Image